Relationships between parameters of uric acid exchange and immunity as well as microbiota in patients with neuroendocrine-immune complex dysfunction - Gozhenko, Anatoliy; Smagliy, Vadym; Korda, Inna; Badiuk, Nataliya; Zukow, Walery; Kovbasnyuk, Marta; Popovych, Igor (Journal of Education, Health and Sport, 2020)
Background. Previously, we found a wide range of uric acid exchange parameters and functional relationships of uricemia and uricosuria with the parameters of immunity in healthy rats analyzed. The purpose of this study is to clarify such relationships in patients with neuroendocrine-immune complex dysfunction on the background of chronic pyelonephritis combined with cholecystitis in remission. Material and Methods. The object of observation were 34 men and 10 women aged 24-70 years old, who came to the Truskavets’ spa for the rehabilitation treatment. The serum and daily urine levels of the uric acid by uricase method were determined. Immune status evaluated on a set of I and II levels recommended by the WHO. The condition of microbiota is evaluated on the results of sowing of feces and urine. Results. The canonical correlation analysis revealed that raw uricemia determines by 28% nine parameters of immunity (relative blood content of pan-lymphocytes and their CD4+-, CD56+-, 0-populations, relative content of polymorphonuclear neutrophils, intensity and completeness of their phagocytosis Staph. aureus and their bactericidal capacity, saliva content of IgG) as well as bacteriuria and content in E. coli feces. Uricemia, normalized by sex and age, determines by 25% another constellation of immunity parameters (relative CD8+ lymphocytes content, CIC, E. coli phagocytosis intensity and completeness, Staph. aureus phagocytosis activity and completeness) as well as content in E. coli feces with impaired enzymatic activity and Klebsiela&Proteus. Instead, uricosuria determines only four parameters of immunity and only by 11,5%. Conclusion. Endogenous uric acid has a modulating overall beneficial effect on a number of immune and microbiota parameters in both healthy rats and people with neuroendocrine-immune complex dysfunction.